Seven days in the art world - Thornton, Sarah (New York Norton, 2008)
The art market has been booming. Museum attendance is surging. More people than ever call themselves artists. Contemporary art has become a mass entertainment, a luxury good, a job description, and, for some, a kind of alternative religion. In a series of narratives, Sarah Thornton investigates the drama of a Christie's auction, the workings in Takashi Murakami's studios, the elite at the Basel Art Fair, the eccentricities of Artforum magazine, the competition behind an important art prize, life in a notorious art-school seminar, and the wonderland of the Venice Biennale. She reveals the new dynamics of creativity, taste, status, money, and the search for meaning in life. A judicious and juicy account of the institutions that have the power to shape art history, based on hundreds of interviews with high-profile players, Thornton's entertaining ethnography will change the way you look at contemporary culture.
The auction -- The crit -- The fair -- The prize -- The magazine -- The studio visit -- The biennale.
Keywords: Art -- Marketing; Art -- Exhibitions; Art -- Competitions; Art auctions; Art criticism